Women of Fes: Ambiguities of Urban Life in Morocco by Rachel Newcomb (Philadelphia: University of Pennsylvania Press, 2009. 248 pages.) (American Journal of Islam and Society, 2010)
The city of Fes, the once “bourgeois citadel” (J. Berque’s words) of Moroccoand once the world’s most populous city (1170-80), has in modernity beenunhappily bypassed for coastal trading hubs and global mega-cities. Materialand symbolic elements of Fassi power persist, however, and anthropologistRachel Newcomb’s finely researched and written ethnography identifies them in upper-middle-class women’s gender identity. In so doing, Women of Fes helps the fields of anthropology, sociology, gender studies, and Islamicstudies to illuminate the often-neglected power of class to shape gender in theMuslim Middle East and North Africa, demonstrating, not pointedly, thatclass divides women within as much as across cultures.Newcomb’s book concerns women of, not merely in, Fes, namely, a classof women of “original” Fassi families navigating the social ruins and newopportunities of daily urban life. Its disparate topics – urban rumors, women’sNGOs, reforms of the Moroccan Muslim family code (mudawanah), flexiblekinship, public space, a dépassé lounge singer – shift the book’s centerfrom class to gender and public life. Her skillful identification of class issueswithin the latter, however, gives the book a necessary coherence ...